Faktor-Faktor Yang Berhubungan Dengan Perilaku Merokok Di Rumah Pada Masyarakat Di Jorong Gantiang Ateh Nagari Tantung Alam Kecamatan Tanjung Baru Kabupaten Tanah Datar Tahun 2013 - Hendri Zoni, Hendri; Suir Syam, Suir Syam (LPPM Universitas Prima Nusantara Bukittinggi, 2013)
Behavior smoke always happened improvement in Indonesia, conducted survey in District plain at twenty two jorong found by case height which smoking at home especially at household headin Jorong Gantiang Ateh.Examinerthis aim to to see Related Factors To Behavior Smoke At Home At Societ in JorongGantian Ateh Region Tanjung Alam Kecamatan Tanjung Baru District Tanah Datar Year 2014. This Research type is quantitative with cross sectional desain. Population in this research is all family head exist in Jorong Gantiang Ateh and technique intake of sampel the used is Systematic Random Sampling with amount populasi 203 people and sampel 67 people. Result of this research there is 62 people smoke at home, 35 ( 52,2%) have negative attitude, 36 (53,7%) explained with cigarette advertisement, and 51 (76,1%) man of means at ugly environment. From result of analysis by using test of chi-square there no hungan between attitude and advertisement smoke with behavior smoke, and there are relation between social environment with behavior smoke, with p value 0,010 â‰¤ Î± ( 0,05). Earning conclusion from three accurate variable do not there are linking between attitude and advertisement smoke with behavior smoke, and there are relation which is signifikan between environment of social with behavior smoke. To be expected to household head in order not to smoke at home so that can improve health of family, and to side of Puskesmas can do construction to family owning household head is smoker.